2021
DOI: 10.1111/jcmm.16461
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism regulator human hydroxysteroid dehydrogenase‐like 2 (HSDL2) modulates cervical cancer cell proliferation and metastasis

Abstract: Human hydroxysteroid dehydrogenase‐like 2 (HSDL2) is a potent regulator in cancers and is also involved in lipid metabolism, but the role of HSDL2 in cervical cancer and whether it regulates the progress of cervical cancer through lipid metabolism remains unclear. In this study, we found that the overexpression of HSDL2 was in relation with cervical cancer progression including lymph nodes metastasis and recurrence. HSDL2 could serve as a novel marker of early diagnosis in cervical cancer. HSDL2 also gave impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…In this study, we detected the expression of HSDL2 in patients with CC. Our results were consistent with a previous research, which HSDL2 was high expressed in the patients with CC [ 23 ]. Then, the correlation between the expression of HSDL2 and miR-26a-5p was analyzed in the CC patients.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, we detected the expression of HSDL2 in patients with CC. Our results were consistent with a previous research, which HSDL2 was high expressed in the patients with CC [ 23 ]. Then, the correlation between the expression of HSDL2 and miR-26a-5p was analyzed in the CC patients.…”
Section: Discussionsupporting
confidence: 94%
“…Our study firstly proved that miR-26a-5p inhibited proliferation, invasion and migration, promoted apoptosis by downregulating the expression of HSDL2 in the CC cells. Combined with Yang’s research [ 23 ], we conclude that miR-26a-5p suppresses proliferation, invasion and migration, promotes apoptosis though inhibiting Epithelial-mesenchymal transition (EMT) by targeting HSDL2 in the CC cells, which supplemented the mechanism of miR-26a-5p-HSDL2-EMT on influencing CC progression.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Dai et al [ 39 ] cloned an HSDL2 gene in mice and found upregulating gene expression after inducement with cholesterol-containing food. Therefore, recent studies have paid more attention to the lipid metabolism of HSDL2 in various cancers [ 38 , 44 , 45 , 46 ]. However, all these studies focused on mammals, and the variability in gene structure among species makes functional differentiation possible.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxysteroid dehydrogenase-like (HSDL) 2 is a member of the short-chain dehydrogenase/reductase (SDR) superfamily that can catalyse the oxidation and reduction of various substrates, such as steroids, sugars, retinoids and fatty acids [ 7 ]. Previous studies have shown that HSDL2 is involved in lipid metabolism and the synthesis of cholesterol [ 8 , 9 ], displaying significant protumour function by promoting cell proliferation and inhibiting apoptosis [ 10 , 11 ], and has been reported to be associated with some cancers, such as pancreatic cancer, breast cancer, and papillary thyroid carcinoma [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%